Do agroforestry systems improve soil functioning? a comparison with other land uses - Pereira, Julia Rossi (2022)
The climatic changes in course impose a series of challenges to agricultural and forestry activities. It is then necessary the search and development of resilient farming systems capable of not only assure food, fiber and fuel production, but that also guarantee the maintenance of ecosystemic processes that are essential to humanity and to other forms of life. As they are critical components of terrestrial ecosystems, soils play important environmental, economic and social functions, and underpin a number of Ecosystem Services through its functioning as well. However, soil is a non-renewable resource at short-term, and it misuse and mismanagement might lead to its depletion, resulting in negative short-medium and long-term impacts. Thus, it is necessary to take a closer look at soil when researching alternative land-use and production systems, in order to better comprehend physical, chemical and biological processes occurring within the soil and how these practices might affect soil attributes and, as a consequence, its functioning. As an alternative to conventional practices, Agroforestry Systems (AF) have been recommended by researches on account of its environmental, social and economic benefits, especially at humid and sub-humid tropical and subtropical zones. In Brazil, highly weathered soil covered by forest formations are predominant, AF arise as good alternatives to simplified monoculture-based agriculture, since they resemble territorys natural conditions. But some ecological benefits of agroforestry practices are still unclear and the great variety of arrangements and practices of AF impose challenges to the total comprehension of its effects over soils. Therefore, this work was drafted in two parts where the first part is a systematic review of scientific literature available on two main databases of worldwide relevance, in order to outline the current scientific knowledge about Agroforestry Systems effects on soils attributes and processes and to identify tits main approaches and shortcomings. And the second part is an analysis of the hydro-physical properties of a soil subjected to four land-use systems (AF, conventional tillage, Eucalyptus forestry and grass fallow), aiming at detecting theses land-use influence over soils superficial layer hydrological functioning, and identify the main differences between them.